Implementasi Pendidikan Karakter dalam Proses Pembelajaran Seni Budaya dan Prakarya (SBdP) Kelas V - Awaluddin Muin; Sitti Jauhar; Muh Idris Jafar; Nurfadhilah Tammah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The problem in this research is the implementation of character education in the learning process of Cultural Arts and Crafts (SBdP) which is still less effective. The approach used in this study is a descriptive qualitative approach. The results of this study indicate that the process of developing character values that occurs in the learning of Cultural Arts and Crafts (SBdP) class V includes the values of nationalist and independent characters. The biggest problems for teachers in developing student character in learning are the carrying capacity of character education at home and in the student's environment, the level of student creativity intelligence in learning, and the lack of supporting facilities and infrastructure for learning. Therefore, the solution that teachers do to overcome these problems is to socialize with parents and the community about the importance of inculcating character values in students, encouraging students to take part in extracurricular and artistic activities, and looking for teaching materials to support learning Arts, Culture and Crafts. (SBdP).